Total versus unicompartmental knee replacement for isolated lateral osteoarthritis: a matched-pairs study - Walker, Tilman; Gotterbarm, Tobias; Bruckner, Thomas; Merle, Christian; Streit, Marcus R. (International orthopaedics, 2014)
PURPOSE: The aim of this study was to compare the functional outcome of patients following unicompartmental knee replacement (UKR) using the Oxford domed lateral UKR to patients who underwent cruciate-retaining total knee replacement (TKR) for isolated osteoarthritis in the lateral compartment. - METHODS: With the help of our institutional database, we retrospectively identified 22 matched pairs with regards to age, gender and body mass index (BMI). Functional outcome was measured using the Oxford Knee Score (OKS) and range of motion (ROM). Complications and revisions were recorded. - RESULTS: The mean follow-up was 22 (UKR) and 19 (TKR) months, respectively. Patients following UKR had a statistically significant higher mean postoperative OKS and ROM: mean OKS was 43 [standard deviation (SD) 4] for UKR and 37 (SD 9) for TKR, respectively (p = 0.023); ROM was 127° (SD 13) for UKR and 107° (SD 17) for TKR (p < 0.001). Additionally the change in score was statistically significant higher in patients following UKR in the OKS (14.3 (SD 6) vs. 9.6 (SD 8)) and in the range of motion (+12° (SD 19) vs. -3° (SD 20)), (p = 0.041 and p = 0.01 respectively). Survival at two years using revision for any reason as the endpoint was 96% [95% confidence interval (CI) 72-99] for UKR and 100% for TKR (Log-rank test, p = 0.317). - CONCLUSION: The functional results of mobile-bearing UKR for isolated osteoarthritis in the lateral compartment compare favourably to those after cruciate-retaining TKR in the short term. To compare survival and complications after both procedures, longer-term follow-up is necessary.
Gesehen am 18.12.2020